Labor Gymnastics: The functionality in the daily life of the Dental Surgeon (Research, Society and Development, 2022)
This study is a qualitative-quantitative research with a descriptive character, which addresses the consequences of long working hours and how they can affect the daily life of the dentists. Since this class acts daily and perform repetitive movements constantly and may suffer from severe pain and Cumulative Trauma Disorders problems in the long term. This present study aims to evaluate the ergonomics and well-being of professionals in their daily lives and identify benefits with the implementation of labor gymnastics at work. Questionnaires were applied in different dental clinics in the city in order to collect information about health and musculoskeletal disorders in order to obtain data for the elaboration of graphs, thus being able to observe results regarding the practice of labor gymnastics in the professional scope. It was observed at the end of this research that gymnastics has the function of adding to dental care, since it allows greater productivity and comfort for the professional.